IMPLEMENTASI PRINSIP KEHATI-HATIAN DALAM PEREDARAN SKINCARE MENGANDUNG MERKURI DAN PRODUK PALSU : STUDI KASUS PADA PLATFORM E-COMMERCE - NIM. A1012171057, SALMA ALYA SHOFWAH (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstrac This study aims to identify efforts that can be made to enhance consumer protection against counterfeit and hazardous skincare products, evaluate the role of e-commerce platforms in ensuring the safety and authenticity of skincare products sold, and formulate policy recommendations and/or best practices to improve the implementation of the precautionary principle in the circulation of skincare on e-commerce platforms. This study employed a descriptive-analytical method by examining primary data (questionnaires and interviews) and secondary data (literature) to understand the relationship between aspects related to the use of skincare containing mercury and counterfeit products without BPOM registration on e-commerce platform users. Samples were selected using purposive sampling and data were collected through Google Forms from 20 respondents. The data were analyzed descriptively to understand the relationships between aspects and provide a comprehensive picture of the results. The research findings indicate that consumers are vulnerable to counterfeit and hazardous skincare products circulating on e-commerce platforms. These products can pose various health risks to consumers, such as skin irritation, allergies, and even poisoning. Therefore, e-commerce platforms have a crucial role in ensuring the safety and authenticity of skincare products sold. However, ecommerce platforms have yet to take adequate steps to combat the circulation of counterfeit and hazardous skincare products. Hence, the precautionary principle needs to be implemented in the circulation of skincare on e-commerce platforms. This principle mandates e-commerce platforms to take reasonable and measurable steps to prevent the circulation of counterfeit and hazardous skincare products. Keywords: Counterfeit and Hazardous Skincare, E-commerce Platform, Precautionary Principle Abstrak Penelitian ini bertujuan untuk mengidentifikasi upaya yang dapat dilakukan untuk meningkatkan perlindungan konsumen terhadap produk skincare palsu dan berbahaya, mengevaluasi peran platform e-commerce dalam memastikan keamanan dan keaslian produk skincare yang dijual, dan merumuskan rekomendasi kebijakan dan/atau praktik terbaik untuk meningkatkan implementasi prinsip kehati-hatian dalam peredaran skincare di platform e-commerce.Penelitian ini menggunakan metode deskriptif analitis dengan meneliti data primer (kuesioner dan wawancara) dan sekunder (kepustakaan) untuk memahami makna hubungan antara aspek-aspek terkait penggunaan skincare mengandung merkuri dan produk palsu tanpa izin edar BPOM pada pengguna platform ecommerce. Sampel dipilih dengan purposive sampling dan data dikumpulkan melalui Google Formulir dari 20 responden. Data dianalisis secara deskriptif untuk memahami hubungan antar aspek dan memberikan gambaran hasil secara utuh. Adapun hasil penelitian menunjukkan konsumen rentan terhadap produk skincare palsu dan berbahaya yang beredar di platform e-commerce. Produk-produk ini dapat menimbulkan berbagai risiko kesehatan bagi konsumen, seperti iritasi kulit, alergi, bahkan keracunan. Sehingga platform e-commerce memiliki peran penting dalam memastikan keamanan dan keaslian produk skincare yang dijual. Namun, platform e-commerce masih belum melakukan langkah-langkah yang memadai untuk memerangi peredaran produk skincare palsu dan berbahaya. Oleh karena itu, prinsip kehati-hatian perlu diterapkan dalam peredaran skincare di platform e-commerce. Prinsip ini mewajibkan platform e-commerce untuk melakukan langkah-langkah yang wajar dan terukur untuk mencegah peredaran produk skincare palsu dan berbahaya.Kata Kunci: Skincare Palsu dan Berbahaya, Platform E-Commerce, Prinsip Kehati-hatian